The impact of party polarization and postmaterialism on voter turnout : a comparative study of 16 industrial democracies - Crepaz, Markus M. L. (European journal of political research : official journal of the European Consortium for Political Research, 1990)
Abstract.
Keywords: poliittinen osallistuminen; puolueet; vaalit; äänestykset